500‐Fold Amplification of Small Molecule Circularly Polarised Luminescence through Circularly Polarised FRET. Issue 1 (1st December 2020) - Wade, Jessica; Brandt, Jochen R.; Reger, David; Zinna, Francesco; Amsharov, Konstantin Y.; Jux, Norbert; Andrews, David L.; Fuchter, Matthew J.
Abstract: Strongly dissymmetric circularly polarised (CP) luminescence from small organic molecules could transform a range of technologies, such as display devices. However, highly dissymmetric emission is usually not possible with small organic molecules, which typically give dissymmetric factors of photoluminescence ( g PL ) less than 10 −2 . Here we describe an almost 10 3 ‐fold chiroptical amplification of a π‐extended superhelicene when embedded in an achiral conjugated polymer matrix. This combination increases the | g PL | of the superhelicene from approximately 3×10 −4 in solution to 0.15 in a blend film in the solid‐state. We propose that the amplification arises not simply through a chiral environment effect, but instead due to electrodynamic coupling between the electric and magnetic transition dipoles of the polymer donor and superhelicene acceptor, and subsequent CP Förster resonance energy transfer. We show that this amplification effect holds across several achiral polymer hosts and thus represents a simple and versatile approach to enhance the g‐factors of small organic molecules. Abstract : The amplification of circularly polarised (CP) luminescence of a small chiral molecule embedded within an achiral polymer matrix is demonstrated. This amplification (from | g PL |=0.0003 to 0.15) is observed in several achiral polymer hosts, due to electrodynamic coupling between the electric and magnetic transition dipoles of the donor (polymer) and acceptor (small molecule), which results in efficient CP Förster resonance energy transfer.